PENDAMPINGAN PRODUKSI PAVING BLOCK BERMUTU PADA INDUSTRI KECIL UD. SAFIRA TARASO - Naumar, Afrizal; Aryanti, Desy; Oktarina, Evince; Auriellia Riafdy, Luthfithary; Aqdi Afrul, Moh.Wal; Rinaldi , Irwandi (Jurnal Teknologi dan Vokasi, 2025)
Small industry UD. Safira Taraso produces paving blocks with various types and types of compressive strength, the most ordered by consumers are the quality of K-250 kg / cm2 and K-225 kg / cm2. Good quality paving blocks have a compressive strength value according to plan and are less than 10% of the absorption value according to SNI 03 - 0691 - 1996. The compressive strength test of paving blocks produced by UD Safira Taraso obtained 139.4 kg / cm2 (11.57 mpa) for the quality of K-225 kg / cm2 and a compressive strength value of 140.6 kg / cm2` (11.67 mpa) for K-250 kg / cm2. Paving block material consists of a mixture of cement, sand, crushed stone, stone ash and water. This material is obtained from the industry and standard testing is carried out in the Teknologi Beton laboratory of Bung Hatta University. This PKM aims to provide assistance and training in the production of paving blocks from the results of the mixture design in the laboratory for the two compressive strengths above. The K250 kg/cm2 mixture design obtained 103 paving blocks with materials of 1 sack of cement, 30.7 kg of sand, 62.1 kg of crushed stone, 63.6 kg of fly ash and 22.3 liters of water. The K225 kg/cm2 mixture design obtained 117 paving blocks with materials of 1 sack of cement, 64 kg of sand, 34 kg of crushed stone, 66.8 kg of fly ash and 28 liters of water. The results of the material mixture design obtained were carried out training and mentoring at the small industry UD. Safira Taraso. Keywords: Pavingblock, Mentoring, Compressive Strength, K225, K250